ANALISIS EFISIENSI PRODUKSI KOPI ARABIKA (Studi Kasus Pada PT. Oro Kopi Gayo Kota Takengon) - Badratun Nafis; Hijri Juliansyah (LPPM Universitas Malikussaleh – Indonesia, 2019)
This study aims to analyze the efficiency of Arabica coffee production at PT Oro Kopi Gayo in Takengon City. This study uses secondary data obtained from the Oro Kopi Gayo company in 2018. The approach used to analyze the data is Data Envelopment Analysis (DEA). The results showed that all villages in the Gayo coffee group have been efficiently demonstrated with a value of 1,000. It indicates that all villages are in the frontier line.